Probiotic Hungatella hathewayi increases host estrogen level via regulation of gut microbiota and host metabolism in sows - Shi, Kai; Zhou, Xiao; Dai, Jiuli; Jia, Jiawei; Dong, Guozeng; Wang, Yongheng; Shen, Yangyang; Chen, Shufang (Frontiers in Microbiology, 2025)
IntroductionAnimal reproduction is a highly complex process influenced by numerous factors, and previous study has suggested that Hungatella hathewayi (HH) may have potential benefits for swine reproduction. Building on these findings, the objective of this study was to investigate the effects of HH supplementation on sows’ hormone levels, antioxidant capacity, host metabolism, and gut microbiota.MethodsTwenty healthy Large-Yorkshire sows with similar physical conditions were randomly divided into four groups based on the principle of similar weight (n = 5). The control group was fed a basal diet, while the treatment groups received the basal diet supplemented with 5 × 1010, 5 × 1011, and 5 × 1012 CFU/sow of HH. Supplementation with HH was administered every three days over a treatment duration of 30 days. Serum and feces of sows were collected at the end of the experiment.ResultsDietary HH supplementation significantly increased the estrogen concentration in sows but did not alter the levels of FSH, progestogen, or antioxidative capacity (T-AOC, SOD, and MDA). 16S rRNA sequencing indicated that HH treatment altered the gut microbial composition and metabolism, increasing the relative abundance of Roseburia, Alloprevotella, Lachnospira, Anaerovibrio, and Hungatella in the HH group. Further metabolomic analysis suggested that the differentially accumulated metabolites from serum and feces involved changes in the metabolism of pyrimidine and tryptophan, as well as alterations in steroid hormone biosynthesis.DiscussionOur findings suggest that dietary supplementation with Hungatella hathewayi has the potential to modulate host estrogen levels through the regulation of gut microbiota and host metabolism. This mechanism may serve as a novel and promising approach for influencing reproductive performance in sows.